SPAWNING OF TWO FRESHWATER MUSSELS UNDER VARIOUS ENVIRONMENTAL CONDITIONS - MISHRA, GAYATRI; JENA, JOYKRUSHNA; KUMAR, K. (Journal of the Inland Fisheries Society of India, 2021)
Lamellidens marginalis and L. corrianus are dioecious with peak spawning occurring during March and August in eastern Indian waters. Few attempts have been made to characterize a suitable treatment that could efficiently stimulate spawning under indoor conditions and also to study the spawning conditions under unfavorable temperature and pH with particular emphasis on their larval survival. Selected physical treatments were heat, cold, alternate heat and cold shocks and chemical treatments viz., aqueous solution of H2 O2 , NaOH, Tris Buffer and NH4 OH. The physical treatments were found to be better in terms of spawning, higher larval survival and longer duration of glochidial viability compared to the chemical stimulus. Key words: Freshwater mussel, spawning, glochidium.